The power spectrum of the Lyman-α Forest at z < 0.5. Issue 1 (17th February 2019) - Khaire, Vikram; Walther, Michael; Hennawi, Joseph F; Oñorbe, Jose; Lukić, Zarija; Prochaska, J Xavier; Tripp, Todd M; Burchett, Joseph N; Rodriguez, Christian
ABSTRACT: We present new measurements of the flux power-spectrum P ( k ) of the z < 0.5 H i Lyman-α Forest spanning scales k 0.001\!-\!0.1 s km^-1 . These results were derived from 65 far-ultraviolet quasar spectra (resolution R 18 000 ) observed with the Cosmic Origin Spectrograph (COS) on board the Hubble Space Telescope . The analysis required careful masking of all contaminating, coincident absorption from H i and metal–line transitions of the Galactic interstellar medium and intervening absorbers as well as proper treatment of the complex COS line-spread function. From the P ( k ) measurements, we estimate the H i photoionization rate (Γ _H I ) in the z < 0.5 intergalactic medium. Our results confirm most of the previous Γ _H I estimates. We conclude that previous concerns of a photon underproduction crisis are now resolved by demonstrating that the measured Γ _H I can be accounted for by ultraviolet emission from quasars alone. In a companion paper, we will present constraints on the thermal state of the z < 0.5 intergalactic medium from the P ( k ) measurements presented here.